Preterm nutrition and brain development - Chiara Nava; Gianluca Lista; Enrica Lupo (BMJ Nutrition, Prevention & Health)
Premature birth puts infants at risk for long-term outcomes, particularly neurodevelopmental impairment. The preterm brain is in a period of extreme vulnerability and fundamental development during hospitalisation in the neonatal intensive care unit. Complications of prematurity cause both direct injury to the preterm brain (e.g., white matter lesions, intraventricular haemorrhage) and altered qualitative and quantitative development of white and grey matter (dysmaturation). Nutrition plays an important role in the neurodevelopment of the preterm infant and the aim of this paper is to summarise the latest evidence on the relationship between nutrition and neurodevelopmental outcomes. For the preterm, as well as for the full-term infant, human milk (HM) appears to be associated with better grey and white matter development at brain magnetic resonance imaging (MRI), which then corresponds to better neurological outcomes in childhood (higher IQ and academic scores). In particular, HM components such as long-chain polyunsaturated fatty acids (LCPUFA) and Human Milk Oligosaccharides (HMOs) appear to play a key role in mediating this influence. As HM nutritional content is insufficient to meet the nutritional needs of most preterm infants, the use of multicomponent fortifiers derived from cow's milk has entered common practice in Neonatal Intensive Care Unit. Although there are promising results concerning the beneficial effects of HM fortifiers on auxological growth, data concerning the effects on neurodevelopment are still uncertain. In the absence of HM, formulas enriched of nutrients such as LCPUFA, HMOs, and sphingomyelin can make the formula more similar to breast milk and has been associated with improved myelination. Higher nutritional intakes of calories and lipids appear to be associated with fewer severe brain lesions and better maturation of white and grey matter. Prebiotics and postbiotics have been extensively studied in recent years for their beneficial effects on the gut and systemic level. In particular through the gut-brain axis it seems that they can regulate the inflammatory response and oxidative stress, mechanisms responsible for neurological damage of preterm infants. Nevertheless, evidence is still lacking on this point. Eventually, current knowledge on the role of micronutrient supplementation (e.g,. iron, lutein, iodine), is still scarce. Further studies are needed to better understand the mechanisms of action of different nutrients on brain development in the preterm infant and thus the effects on long-term neurological outcomes.